Manifestasi Kelainan Paru pada Lupus Eritematosus Sistemik: Tinjauan Pustaka - Apriance, Yessi; Kurniati, Roza; Fauzar (Cermin Dunia Kedokteran, 2025)
Systemic lupus erythematosus (SLE) is an autoimmune disorder with a very dynamic course and various clinical manifestations. With respiratory tract involvement in 50%-70% of patients, pulmonary disorders are one of the causes of the high morbidity and mortality in SLE patients. The high mortality in SLE patients with pulmonary disorders contribute to patients' survival with a hazard ratio of 3.13. This article discusses the manifestations of pulmonary disorders in SLE patients.